Comparison of Oral Trichlophos and Intranasal Midazolam for Sedation in Minimally Invasive Paediatric Procedures (RAMT Study) - Sharma, Manoj; Yenamandra, Kamal K.; Kalita, Jitu; Dash, Shaswat; Singh, Daljit (Journal of Nepal Paediatric Society, 2019)
Introduction: Uncooperative child does not allow completion of procedures, denying valuable data required for clinicians. Material and Methods: An open labelled parallel group prospective randomized control study was conducted at zonal hospital Jorhat. We evaluated 200 children randomized into two groups using computer based randomization. Participants aged 3 months to 5 years (n=200) were randomized to receive 50 mg/kg Triclofos sodium orally or intranasal spray of midazolam 0.2 mg/kg. Results: Adequate sedation (Ramsay reactivity score of 3 and 4) was obtained in 86% children in midazolam group as compared to 80% in triclofos group with p value of 0.138. Mean duration for onset of sedation was 20 min ± 5.4 min in Trichlophos group and 12 min ± 4.5 min with Intranasal Midazolam which was statistically significant with p-value of <0.001. The mean duration of post procedural sedation was found to be 24.00 ± 9.21 min in midazolam group and 49.00 ± 16.99 min in triclofos group (p=<0.001) which was statistically significant. No significant difference was seen for side effects frequency between the two drugs (15% in Triclofos, 10% in Midazolam group; p=0.285). Conclusion: We conclude that intranasal midazolam is more effective than oral trichlophos with a comparable safety profile. CTRI Trial Number: /2017/08/009448.